Teacher Professional Ethics as a Foundation for Culture-Based Pedagogy in Fostering Peaceful Primary Schools: A Systematic Literature Review - Nabilla Fissalma; Oktaviani Adhi Suciptaningsih; Ade Eka Anggraini; Intan Sari Rufiana; Mardhatillah; Aynin Mashfufah; Slamet Arifin (Elementary Teacher Education Program, Majalengka University, 2026)
The modern era is characterized by the complexity of a pluralistic culture that requires teachers to act as educators, moral guardians, and facilitators in the learning environment. This challenge requires a foundation of scientific ethics and a contextual learning approach. This study aims to systematically examine scientific ethics as a moral foundation and strategic filter in fostering cultural diversity in elementary schools. The method used is a Systematic Literature Review. Data were collected and analyzed from 16 scientific articles published in 2021-2025, using the PRISMA guidelines from the Google Scholar and ScienceDirect indexed databases. The results of the study show that scientific ethics serve as a moral compass that guides every decision and interaction in the classroom through eight prerequisites of professionalism. Scientific ethics directs the application of a culture-based approach as an effective pedagogical strategy for fostering diversity. The synergy between scientific ethics and a cultural approach is the basis for realizing peaceful schools through three main prerequisites: the moral integrity of educators, pedagogical approaches, and collaboration between teachers, parents, and the community. A cultural approach supported by a strong ethical foundation can help connect the curriculum to students' lives, fostering tolerance, empathy, and mutual cooperation. Thus, this study not only discusses the relationship between scientific ethics and culture-based approaches but also provides a novelty in the form of a conceptual model of the synergy between the two as a pedagogical foundation for multicultural education in an independent curriculum.